Marco conseptual de una cultura sistémica en las redes virtuales de fabricación global - J. R. Vilana Arto; Carlos Rodríguez Monroy (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2010)
This paper analyzes the most relevant factors of organizational culture that appear in Global Manufacturing Virtual Networks (GMVNs). These organizations are formed by highly dynamic manufacturing companies, that may even be even competitors, which establish horizontal and vertical relations among themselves, and where it is not necessary to maintain internally many manufacturing assets but to manage and share efficiently network resources. This study of organizational culture at the network level includes aspects such as the similarity of cultural practices, social embeddedness, tacit knowledge transfer or the importance of trust in the network. By using the proposed theoretical model, it will analyzed the presence, under a systemic perspective, of homogeneous values and cultural practices where network actors can feel indentified. Finally, in order to validate the proposed model, the case methodology will be applied to one of the most successful collaborations of GMVNs within the aeronautics industry, the collaboration between GE and SNECMA to manufacture the CFM56 engine.
Keywords: L14; M14; 330; global manufacturing virtual networks; inter-organizational culture; aeronautics industry